Validity and Reliability of the Polish Adaptation of the CHAMPS Physical Activity Questionnaire - Król-Zielińska, Magdalena (Biomed Res Int, 2019)
The aim of the study was to investigate the reliability and construct validity of the Polish adaptation of the Community Health Activities Model Program for Seniors (CHAMPS) physical activity questionnaire among the elderly. The sample included 104 volunteers, 75 women (age = 71.0 ± 5.0 years) and 29 men (age = 75.1 ± 6.6 years). To assess the reliability of the Polish version of the CHAMPS physical activity questionnaire, measurements were conducted by one-week test-retest. The construct validity of the CHAMPS physical activity questionnaire was evaluated using accelerometers. Criterion validation was verified by self-reported measurements (health self-assessment, life satisfaction, and wellbeing) and body composition analysis. Intraclass correlation coefficients of the one-week test-retest ranged from 0.79 to 0.85. Significant Pearson's correlations were found between caloric expenditure measured by accelerometer and CHAMPS caloric expenditure in all listed physical activities (r = 0.33) and caloric expenditure in at least moderate intensity physical activities (r = 0.37) of the CHAMPS physical activity questionnaire. Moderate and greater intensity physical activities of CHAMPS measure were significantly related to total bone mass, health self-assessment, life satisfaction as a whole, and personal wellbeing (r ranged from 0.26 to 0.34). The findings of the study allow us to conclude that the Polish version of the CHAMPS physical activity questionnaire has acceptable reliability and validity to assess physical activity of older adults.